Advanced topics in global informtion management - Hunter, M. Gordon (IGP, 2004)
Advanced Topics in Global Information Management is the third in a series of books on advance topics in global information management (GIM). GIM research continues to progress, with some scholars pushing the boundaries of thinking and others challenging the status quo. *Note: This book is part of a new series entitled "Advanced Topics in Global Information Management". This book is Volume Three within this series (Vol. III, 2004).